'Dance to Health': an evaluation of health, social and dance interest outcomes of a dance programme for the prevention of falls. Issue 2 (4th May 2021) - Vella-Burrows, Trish; Pickard, Angela; Wilson, Lian; Clift, Stephen; Whitfield, Laura
ABSTRACT: Background : Falls and related injuries in the older population are major public health issues requiring more innovative and effective solutions. This paper reports an evaluation of the Dance to Health (DtH) programme which integrates evidence-based physiotherapy falls-prevention exercises into creative dance. Methods : Sixty-seven participants took part in a mixed-methods study that combined focus group discussions and six pre/post-test questionnaires with a focus on dance interest and ability, group identity, loneliness and isolation, general health and mental health. Results : The findings show that the DtH programme can support and enhance physical, mental and social health and levels of interest in dance. The mixed data yielded evidence of positive change, with statistical significance in findings relating to group bonding and improved physical control and coordination. Conclusions : The findings support the case for recommending the Dance to Health programme in falls-prevention services in relation to its ability to promote a wide range of health and wellbeing benefits.